“SOCIALIST IN FORM, NATIONAL IN CONTENT”: THE REVIVAL OF THE NAŪRYZ HOLIDAY IN LATE 1980S KAZAKHSTAN - Xan, Gulzada (Nazarbayev University School of Sciences and Humanities, 2025)
Naūryz, the spring equinox holiday and one of the key events on Kazakhstan’s cultural calendar, was absent from public life for more than sixty years. It was officially revived only in the spring of 1988. While the return of Naūryz has received increasing attention in the local media for the last five years, academic research on the topic remains limited. Existing scholarship on late Soviet Kazakhstan has mostly focused on political protests like Jeltoqsan events, environmental activism like the Nevada-Semey movement, and broader cultural reforms, leaving a gap in understanding how traditions like Naūryz were brought back into public life. This research studies the revival of Naūryz between 1988 and the early 1990s, arguing that the holiday was initially reimagined within the ideological framework of being “Socialist in Content, National in Form.” Early celebrations praised perestroika and emphasized Soviet values, including collective labor, friendship of nations, and ecological awareness. However, over time local intellectuals began to shift the narrative toward national history and cultural heritage. As a result, by the early 1990s, Naūryz was increasingly framed as “National in Content, Soviet in Form,” with greater emphasis on pre-Soviet traditions and Kazakh cultural identity. Using the archival documents, media materials, and literary sources, this study analyzes how Naūryz was framed, performed, and institutionalized through the lens of invented traditions and imagined communities.
Keywords: Nauryz; Kazakhstan; revival; invented tradition; Soviet Union; national identity; cultural policy; late socialism.; type of access: open access